2017
DOI: 10.1016/j.joto.2017.08.001
|View full text |Cite
|
Sign up to set email alerts
|

Apoptosis in inner ear sensory hair cells

Abstract: Apoptosis, or controlled cell death, is a normal part of cellular lifespan. Cell death of cochlear hair cells causes deafness; an apoptotic process that is not well understood. Worldwide, 1.3 billion humans suffer some form of hearing loss, while 360 million suffer debilitating hearing loss as a direct result of the absence of these cochlear hair cells (Worldwide Hearing, 2014). Much is known about apoptosis in other systems and in other cell types thanks to studies done since the mid-20th century. Here we rev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(29 citation statements)
references
References 160 publications
0
29
0
Order By: Relevance
“…Typically, LMRs tend to be enriched for H3K4me1, DNase I hypersensitive sites (DHS) and p300/CBP. We identified 31,916,17,945 and 31,564 UMRs and 174,347,237,282 and 206,144 LMRs in E16.5, P0 and P22 methylomes, respectively ( Fig. 1c; Additional file 2: Table S1), which have the expected percent methylation and genome localization characteristics (Additional file 1: Figure S1c-h).…”
Section: Regulatory Landscape Of the Inner Ear Sementioning
confidence: 92%
See 1 more Smart Citation
“…Typically, LMRs tend to be enriched for H3K4me1, DNase I hypersensitive sites (DHS) and p300/CBP. We identified 31,916,17,945 and 31,564 UMRs and 174,347,237,282 and 206,144 LMRs in E16.5, P0 and P22 methylomes, respectively ( Fig. 1c; Additional file 2: Table S1), which have the expected percent methylation and genome localization characteristics (Additional file 1: Figure S1c-h).…”
Section: Regulatory Landscape Of the Inner Ear Sementioning
confidence: 92%
“…Interestingly, we found that a Bach2 motif was significantly enriched across all time points (E16.5, P0 and P22, p = 1x10 -9 , 1x10 -16 , 1x10 -76 , respectively). This TF plays a role in the Bcl6-Bcl2-p53 axis in controlling apoptosis in several non-inner ear tissue types (reviewed in [31]), as well as has late onset expression in the developing chick ridge, otic cup and/or neural crest [32]. However, Bach2 has not been reported to play a role in the inner ear development.…”
Section: Regulatory Landscape Of the Inner Ear Sementioning
confidence: 99%
“…In the adult inner ear, apoptosis is a crucial mechanism to maintain neuronal and sensory cell populations, being this a field of renewed research interest to identify drug-targets and develop novel therapies to prevent cell death and hearing loss (Morrill and He, 2017;Wang and Puel, 2018).…”
Section: Autophagy (C-d)mentioning
confidence: 99%
“…This system of epithelially lined channels and spaces is filled with endolymph (Scarpa's fluid); the utricular duct, the saccular duct, and the ductus reuniens interconnect the major structures [18].…”
Section: The Membranous Labyrinthmentioning
confidence: 99%
“…The scala media filled with end lymph, which resemble intracellular fluid (low in sodium, high in potassium) in composition. The electrolyte composition of the scala media causes the endocochlear potential, which is +60 to +100 mV relative to the perilymph [18].…”
Section: Cochlea Figure 7: Cochlea [18]mentioning
confidence: 99%